GENETIC ENGINEERING OF TOMATO PLANTS: A NARRATIVE REVIEW OF THE UTILIZATION OFAGROBACTERIUM AND CRISPR-CAS9 - Anatasya Putri Gusasi; Titania Rahma Aureria Inaku; Saputri Afra A. Pakaya; Nur Fadilah Sahran; Sintia ABD Rahman; Natasya Aprilia Putri Supardi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Global population growth increases the demand for nutritious food, while tomato (Solanum lycopersicum L.) productivity often declines due to biotic and abiotic stress. CRISPR/Cas9 technology offers a precision approach to improving the nutritional quality, disease resistance, and metabolic efficiency of tomatoes. This review analyzes research from 2015 to 2025 on gene editing related to vitamin C enhancement, leaf morphology modification, fruit ripening, and strengthening resistance to pathogens such as TYLCV and powdery mildew, with Agrobacterium-based transformation proven effective in producing stable changes. However, challenges such as off-target risks and limited access to technology remain obstacles. Overall, CRISPR/Cas9 has the potential to accelerate tomato variety improvement for global food security, but further research is needed to enhance the precision and sustainability of its development.